2015
DOI: 10.18632/oncotarget.4032
|View full text |Cite
|
Sign up to set email alerts
|

Genomic instability and cellular stress in organ biopsies and peripheral blood lymphocytes from patients with colorectal cancer and predisposing pathologies

Abstract: Inflammatory bowel disease (IBD) and polyps, are common colorectal pathologies in western society and are risk factors for development of colorectal cancer (CRC). Genomic instability is a cancer hallmark and is connected to changes in chromosomal structure, often caused by double strand break formation (DSB), and aneuploidy. Cellular stress, may contribute to genomic instability. In colorectal biopsies and peripheral blood lymphocytes of patients with IBD, polyps and CRC, we evaluated 1) genomic instability us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The role for STAT3 in carcinomas remains controversial - nuclear STAT3 (pYSTAT3) is regarded as a biomarker for prognosis prediction in solid tumours [20]. Several studies reported elevated and tumor promoting STAT3 signaling in CRC [5, 6, 7, 21]. In contrast, others have reported that STAT3 suppresses CRC [15, 22].…”
Section: Discussionmentioning
confidence: 99%
“…The role for STAT3 in carcinomas remains controversial - nuclear STAT3 (pYSTAT3) is regarded as a biomarker for prognosis prediction in solid tumours [20]. Several studies reported elevated and tumor promoting STAT3 signaling in CRC [5, 6, 7, 21]. In contrast, others have reported that STAT3 suppresses CRC [15, 22].…”
Section: Discussionmentioning
confidence: 99%
“…The GSTO1 upregulation has been reported in different cancers, including bladder [35], pancreatic, ovarian cancer [24,36] and esophageal adenocarcinoma [37]. Moreover, nuclear localization of GSTO1 in Barrett's esophagus [38] and colorectal carcinoma [39] suggests its probable involvement in the protection of specific nuclear components in conditions of oxidative stress, thus promoting malignant transformation. Unfortunately, there are no literature data on GSTO2 expression in cancer, as yet.…”
Section: Discussionmentioning
confidence: 99%
“…GSTO1-1 has been implicated in the regulation of oxidative stress and inflammation in various organ systems, where both overexpression and polymorphisms in the encoding gene have been linked to pathological diseases, including cancer, and neurological disorders. [5][6][7][8][9] GSTO1-1 is required for lipopolysaccharide (LPS)-mediated inflammatory responses in macrophages, inducing reactive oxygen species (ROS) production and proinflammatory cytokine expression through the toll-like receptor 4 (TLR4) pathway. 10,11 GSTO1-1-deficient macrophages consequently demonstrate lower levels of oxidative stress and inflammation.…”
mentioning
confidence: 99%